Stakeholder theory in urban management: an in-depth investigation on stakeholder types, salience, cooperation, managerial values, and urban quality of life - Beck, Donizete Ferreira (2023)
The purpose of this doctoral dissertation is to understand what is the relationship between urban performance and stakeholder salience in urban management. In order to achieve this purpose, this doctoral dissertation was divided into three studies. In the first study, I identified and mapped the intellectual structure and mainstream research on stakeholder theory in the context of urban management by performing bibliometrics using co-citation analysis, bibliographic coupling, and social network analyses of both data on the intellectual structure and mainstream research. I revealed how the intellectual structure has evolved from its two components - urban strategy and urban marketing - into three components of mainstream research - sustainable urban strategy, power of networks, and urban marketing. In the second study, I identified and discussed the construct of stakeholder proposed by Freeman in 1984 in the context of municipal urban management through a review of the mainstream research on stakeholder theory in urban management. There are two main approaches to analyzing urban stakeholders - the typological and the general one. On the one hand, the typological approach splits urban stakeholders into categories; there are twelve main types of urban stakeholders, which are in order of the number of occurrences in literature: (1) governments; (2) industry; (3) citizens; (4) civil society; (5) tourists; (6) academia; (7) union; (8) media; (9) investors; (10) financial institutions; (11) suppliers; and (12) supranational and international organizations. On the other hand, the general approach emphasizes the role of urban projects and partnerships by urban managers instead of separating stakeholders into different types. Finally, in the third study, I analyzed the salience (mediator variable) of four urban-stakeholder types (government, industry, citizens, and civil society) as perceived by urban managers, urban quality of life (dependent variable), and managerial values (independent variable), and stakeholder collaboration (moderator variable), in an integrative model in the urban context. For this, a research model was tested through Bayesian Correlation and Bayesian Regression of 85 responses from a survey collected in 24 cities from Brazil, the United States, and Israel. In this study, I did not identify any statistical relationship between stakeholder salience and urban quality of life, and managerial values did not moderate that relationship. Nonetheless, findings revealed a positive relationship between self-regarding values and stakeholder power and between other-regarding values and legitimacy. The originality of this study is to reveal that there is a possibility of self-regarding values (egoistic culture) and power as well as other-regarding values (altruistic/moralist culture) and legitimacy, two existing relationships disregarding the organizational type. However, further studies should be done to affirm this universality. Also, I proposed a comprehensive agenda for future studies in the three studies.